Intervention strategies for microbial therapeutics in cancer immunotherapy. (June 2020) - Gopalakrishnan, V.; Weiner, B.; Ford, C.B.; Sellman, B.R.; Hammond, S.A.; Freeman, D.J.; Dennis, P.; Soria, J-C.; Wortman, J.R.; Henn, M.R.
Abstract : Immunotherapies have drastically improved clinical outcomes in a wide range of malignancies. Nevertheless, patient responses remain highly variable, and reliable biomarkers that predict responses accurately are not yet fully understood. Compelling evidence from preclinical studies and observational data from clinical cohorts have shown that commensal microorganisms that reside in the human gastrointestinal tract, collectively termed the 'microbiome', can actively modify responses to chemotherapeutic agents and immunotherapies by influencing host immunosurveillance. Notably, microbial correlates are largely context specific, and response signatures may vary by patient population, geographic location and type of anticancer treatment. Therefore, the incongruence of beneficial microbiome signatures across studies, along with an emerging understanding of the mechanisms underlying the interactions between the microbiome, metabolome and host immune system, highlight a critical need for additional comprehensive and standardized multi-omics studies. Future research should consider key host factors, such as diet and use of medication, in both preclinical animal models and large-scale, multicenter clinical trials. In addition, there is a strong rationale to evaluate the microbiome as a tumor-extrinsic biomarker of clinical outcomes and to test the therapeutic potential of derived microbial products (e.g. defined microbial consortia), with the eventual goal of improving the efficacy of existing anticancer treatments. This review discusses the importance of the microbiome from the perspective of cancer immunotherapies, and outlines future steps that may contribute to wide-ranging clinical and translational benefits that may improve the health and quality of life of patients with cancer. Highlights: The gut microbiome impacts the outcomes of cancer treatment by influencing host immunosurveillance. Modulation of microbiota represents a novel therapeutic strategy to improve responses. Incongruent beneficial bacterial signatures complicate the design of modulators. Reverse translation processes can be used to characterize candidate bacteria. Rationally designed microbial consortia catalyze transition to a healthy ecology.